Love, power, and gender in seventeenth-century French fairy tales - Reddan, Bronwyn (University of Nebraska Press, 2020)
Introduction: Reimagining Fairy-Tale Love – Part 1. Formation of a Literary Emotional Community (1. The Creation of a Female Literary Community; 2. A Shared Vocabulary of Love) – Part 2. Conversations about Love (3. Courtship, Consent, and Declarations of Love; 4. Marriage, Gift-Giving, and the Obligation of Love; 5. Love after Marriage: Moral Lessons and Unhappy Endings) – Conclusion: Truth-Finding in Fairy Tales.
Includes bibliographical references and index
Keywords: Fairy tales; French fiction; Women and literature; Courtship in literature; Marriage in literature; Love in literature